Impacts of Courtyard Geometrical Configurations on Energy Performance of Buildings - Almhafdy, Abdulbasit; Ibrahim, Norhati; Sh Ahmad, Sabarinah (Environment-Behaviour Proceedings Journal, 2019)
The courtyard is an architectural design element often regarded as microclimate modifiers.Â It has the potential of improving comfort conditions within the outdoor courtyard space and the enclosing indoor spaces. Harnessing the optimum benefits of courtyards depends on several conditions namely the orientation and configurations of the courtyards, as well as the treatment of the external surfaces of the enclosing building envelopes. As three variables of orientation, number of floors and wall envelope have not been investigated in a single study, therefore, this parametric study was performed to investigate the microclimatic influence of varying courtyard geometric configurations and its enclosing facades in hot and humid climate using IES<VE> simulation tools.Â The study observed the environmental impact regarding thermal performance and energy consumption of the enclosing indoor spaces.Â The results suggest optimum conditions to harness the potential of courtyards to lower energy consumption of buildings in the tropics. Keywords: courtyard; thermal performance; energy consumption; simulation eISSN: 2398-4287 Â© 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i10.1637 Â